Bibliometric analysis of research trends in college students' mobile phone addiction from 2013 to 2023 - Wang, Ruifeng; Abd Karim, Sairah; Tham, Jacquline (Intelektual Pustaka Media Utama, 2025)
Mobile phone addiction (MPA) among college students is a growing concern affecting physical and mental well-being. This study employs CiteSpace 6.2.R6 to analyze research trends on MPA. A total of 957 articles published between 2013 and 2023 were analyzed, with key contributors including Griffiths, Mark D, and institutions like Nottingham Trent University and Toledo University.